The Effectiveness of Online Examination Based on Google Form on Art Culture Class Students Subject in SMP Negeri 2 Baranti - Bahar, Nur Fajrah; M, Usman; Kahar, Abdul; Hermansyah, Sam (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2023)
This study is to determine the effectiveness of google form-based online exams in cultural arts subjects of seventh grade students of SMP Negeri 2 Baranti, Sidenreng Rappang Regency. The population of this study were all seventh grade students of SMP Negeri 2 Baranti, Sidenreng Rappang Regency, a total of 137 people, and the sample taken was 28 people, and this study used non-probability sampling. The data collection techniques used were observation techniques, documentation techniques and questionnaire techniques. The effectiveness indicators in this study are based on Sinambella's theory, the three effectiveness indicators are: learning completeness, timeliness, and student response. Testing the research hypothesis, data analysis obtained a percentage of 85% ability for learning completeness, timeliness is said to be effective because the time given is sufficient for taking the exam and for the student response obtained 100% results this can be seen from the completion of the exam and the questionnaire that has been distributed link. Based on the results of this study, it shows that the effectiveness of Google Form-based online exams in cultural arts subjects for seventh grade students of SMP Negeri 2 Baranti, Sidenreng Rappang Regency in the 2022/2023 school year